2017
DOI: 10.1038/gim.2016.53
|View full text |Cite|
|
Sign up to set email alerts
|

The phenotypic spectrum of Schaaf-Yang syndrome: 18 new affected individuals from 14 families

Abstract: PurposeTruncating mutations in the maternally imprinted, paternally expressed gene MAGEL2, which is located in the Prader-Willi critical region 15q11-13, have recently been reported to cause Schaaf-Yang syndrome, a Prader-Willi-like disease, manifesting developmental delay/intellectual disability, hypotonia, feeding difficulties, and autism spectrum disorder. The causality of the reported variants in the context of the patients’ phenotypes was questioned, as MAGEL2 whole gene deletions appear to cause little t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
161
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(170 citation statements)
references
References 16 publications
6
161
1
2
Order By: Relevance
“…Proband information is summarised in table 1. Patients 1, 7 and 8 of this study had been reported previously as patients 2, 3, and 1, respectively, by Fountain et al 4. Patients 3 and 5 of this study had been reported previously as patients CMH383 and CMH382 by Soden et al 7.…”
Section: Methodssupporting
confidence: 62%
“…Proband information is summarised in table 1. Patients 1, 7 and 8 of this study had been reported previously as patients 2, 3, and 1, respectively, by Fountain et al 4. Patients 3 and 5 of this study had been reported previously as patients CMH383 and CMH382 by Soden et al 7.…”
Section: Methodssupporting
confidence: 62%
“…Several de novo truncating mutations, similar to the one described here, have been reported previously in patients with Schaaf-Yang syndrome (SHFYNG, MIM #615547)67, a condition with some resemblances to Prader-Willi syndrome, and in two patients with a distinct severe arthrogryposis phenotype8. Very recently, Fountain et al 9. described 18 additional SHFYNG patients with similar mutations.…”
supporting
confidence: 78%
“…10 for further comparisons), and in patients with a severe form of arthrogryposis with reduced fetal movement and perinatal death8. Recently, Fountain et al 9,. described a large series of SHFYNG patients, all with a truncating MAGEL2 mutation on the paternal chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…The variant was not present in parents or unaffected siblings, and was determined to be on the paternal allele (online supplementary figure 4). Patient 4-I has a previously reported frameshift insertion (c.1996dupC(p.Gln666Profs*47))6 in MAGEL2 , inherited from her unaffected father.…”
Section: Sequencing Resultsmentioning
confidence: 99%